Beyond Human Law: Rethinking Forest Fire Governance Through a Posthumanist Lens in Indonesia’s Peatland Frontiers - Munte, Hengky Fransiscus; Mulyadi, Aras; ., Nofrizal; ., Erdianto (Journal of Posthumanism, 2025)
Forest fires in Indonesia, particularly in Riau Province’s peatland regions, are often addressed through punitive legal frameworks that center on human accountability. However, such anthropocentric approaches overlook the complex entanglements between legal systems, ecological dynamics, and non-human actors such as fire, peat, and atmosphere. This study employs a posthumanist perspective to explore the limits of current forest fire governance and the potential for rethinking law as a relational and ecological practice. Using a mixed-methods design including qualitative field observation and quantitative SWOT analysis the research examines legal enforcement, environmental impacts, and institutional capacities in Pelalawan Regency. Findings reveal that law enforcement remains reactive and fragmented, failing to address the multispecies nature of fire events. The study proposes a shift from human-centered legality toward a more-than-human legal ecology that recognizes forests not merely as resources, but as co-constituents of justice. By foregrounding multispecies interdependence, this work contributes to emerging debates on environmental ethics, legal pluralism, and ecological governance in the Anthropocene